Решите уравнение, используя введения новой переменной (2x^2+x-1)(2x^2+x-4)+2=0

RMaGaR RMaGaR    2   26.05.2019 18:10    0

Ответы
vika2499 vika2499  23.06.2020 06:12
Пускай 2x^{2}+x=y, тогда (у-1)*(у-4)+2=0, y^{2}-5y+4+2=0, y^{2}-5y+6=0, D=25-4*6=1, y1=(5-1)/2=2, y2=(5+1)/2=3. 2x^{2}+x=2, 2x^{2}+x-2=0, D=1-4*2*(-2)=17, x1=(-1-\sqrt{17})/(2*2)=(-1-\sqrt{17})/4, x2=(-1+\sqrt{17})/4. 2x^{2}+x=3, 2x^{2}+x-3=0, D=1-4*2*(-3)=25, x3=(-1-5)/(2*2)=-1,5, x4=(-1+5)/4=1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра